Area-selective passivation of sp2 carbon surfaces by supramolecular self-assembly. Issue 16 (10th April 2017) - Li, Zhi; Van Gorp, Hans; Walke, Peter; Phan, Thanh Hai; Fujita, Yasuhiko; Greenwood, John; Ivasenko, Oleksandr; Tahara, Kazukuni; Tobe, Yoshito; Uji-i, Hiroshi; Mertens, Stijn F. L.; De Feyter, Steven
Abstract : Monolayer-thin self-assembled alkanes on graphitic substrates form an effective barrier against covalent grafting by radicals. Abstract : Altering the chemical reactivity of graphene can offer new opportunities for various applications. Here, we report that monolayers of densely packed n -pentacontane significantly reduce the covalent grafting of aryl radicals to graphitic surfaces. The effect is highly local in nature and on fully covered substrates grafting can occur only at monolayer imperfections such as interdomain borders and vacancy defects. Grafting partially covered substrates primarily results in the covalent modification of uncoated areas.